SERANGGA-SERANGGA HAMA PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) DI DESA DUNU KECAMATAN MONANO KABUPATEN GORONTALO UTARA PROVINSI GORONTALO - Fransisca Indriani Tahir; Jusuf Manueke; Redsway Truman Douglas Maramis (COCOS, 2022)
ABSTRACT This study aims to determine insect pests on cayenne pepper (Capsicum frutescent L.) in Dunu Village, Monano District, North Gorontalo Regency, Gorontalo Province. This research was carried out for three months, from April to June 2021. The research method used was descriptive exploratory with 2 stages, namely sampling in the field and observations in the laboratory which were then presented in descriptive form in the form of tables, pictures, and graphs. Samples were obtained by catching using light traps and nets carried out for 6 consecutive days on 500 m2 area of cayenne pepper which was used as an experimental or observation area. The area consists of 1 light trap which is placed in the cayenne pepper plant and the lights are turned on every day from 18:00-06:00 WITA, then nets are used at 06:00-07:00 WITA and 16:00-18:00 WITA with the help of hands. Insects caught were taken and then observed the type and number of insects. Based on the results of research conducted, it showed that 8 types of insect pests were found, namely Nezara sp., Faneroptera sp., Gryllus sp., Acrida sp., Valanga sp., Bactocera sp., Circulifer sp., which belong to 4 orders and 6 families. The number of individuals found was 454 individuals, the highest was in the genus Nezara sp. namely 138 individuals and the lowest in the genus Gryllus sp. namely 11 individuals. Keyword : Insect, Pests, Cayenne pepper